Size dependence of the Superconducting critical temperature and fields of Nb/Al multilayers - Guimpel, J. (1986)
Fil: Guimpel, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina